An attenuated Machupo virus with a disrupted L-segment intergenic region protects guinea pigs against lethal Guanarito virus infection - Joseph W. Golden (Nature Portfolio, 2017)
Abstract Machupo virus (MACV) is a New World (NW) arenavirus and causative agent of Bolivian hemorrhagic fever (HF). Here, we identified a variant of MACV strain Carvallo termed Car91 that was attenuated in guinea pigs. Infection of guinea pigs with an earlier passage of Carvallo, termed Car68, resulted in a lethal disease with a 63% mortality rate. Sequencing analysis revealed that compared to Car68, Car91 had a 35 nucleotide (nt) deletion and a point mutation within the L-segment intergenic region (IGR), and three silent changes in the polymerase gene that did not impact amino acid coding. No changes were found on the S-segment. Because it was apathogenic, we determined if Car91 could protect guinea pigs against Guanarito virus (GTOV), a distantly related NW arenavirus. While naïve animals succumbed to GTOV infection, 88% of the Car91-exposed guinea pigs were protected. These findings indicate that attenuated MACV vaccines can provide heterologous protection against NW arenaviruses. The disruption in the L-segment IGR, including a single point mutant and 35 nt partial deletion, were the only major variance detected between virulent and avirulent isolates, implicating its role in attenuation. Overall, our data support the development of live-attenuated arenaviruses as broadly protective pan-arenavirus vaccines.